Efficacy and safety of tripterygium glycosides combined with ACEI/ARB on diabetic nephropathy: a meta-analysis - Zhuan’E. Yao; Zhuan’E. Yao; Pengbo Wang; Qinjuan Fu; Qiong Song; Haojian Xu; Peng Zhang (Frontiers in Pharmacology)
AimsThis study aims to evaluate the efficacy and safety of tripterygium glycosides combined with angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARBs) in treating Diabetic nephropathy and provide high-level evidence to support its standardized application.MethodsLiteratures were retrieved from PubMed, Web of Science, EMBASE, Cochrane Library, CNKI, Wanfang and VIP databases, the search time frame was defined as from the time of establishment to April 2023. This study only included randomized controlled trials of tripterygium glycosides combined with ACEI/ARB in the treatment of diabetic nephropathy, and the final included studies were identified according to the inclusion and exclusion criteria, and meta-analysis of data was performed using RevMan 5.3 software.ResultsA total of 44 RCTs with 3537 DN patients were included in the study. Compared with the control group, tripterygium glycosides combined with ACEI/ARB significantly reducing 24 h-UTP (24 h urine total protein) [SMD = −1.46, 95% CI (−1.70, −1.23), P < 0.00001], increasing effective rate [RR = 1.23, 95% CI (1.17,1.29), P < 0.00001], elevating serum albumin [SMD = 0.85, 95% CI (0.69, 1.02), P < 0.00001], improving serum creatinine [SMD = −0.35, 95% CI (−0.59, −0.11), P = 0.004], with no difference in BUN (blood urea nitrogen) [SMD = −0.17, 95% CI (−0.48,0.13), P = 0.27], the adverse reactions rate was higher than those of the control group [RR = 1.96, 95%CI (1.43, 2.68), P < 0.0001].ConclusionThis study showed that the combination of tripterygium glycosides and ACEI/ARB was more effective than ACEI/ARB alone. However, the side effects of the combined treatment group were higher than those of the control group, especially liver function damage, which also suggested that its safety in the treatment of diabetic nephropathy was worth considering. Therefore, although tripterygium glycosides provided a choice for the clinical treatment of diabetic nephropathy, its side effects limited its clinical application. In future studies, we need to further optimize tripterygium glycosides and reduce its side effects to ensure the safety of clinical application.